Introduction to Sociocybernetics (Part 2): Power, Culture and Institutions - Mancilla, Roberto Gustavo (Journal of Sociocybernetics, 2013)
The purpose of this article is to understand, from the perspective of third order cybernetics, three important and well regarded subjects in sociology and political science: Power, Culture and Institutions. Regarding the study of power, four questions will be asked: What is it? What is its exercise? Who exercises it? And how it is exercised? To answer the first, a typology of power will be produced, the second question is answered by means of the distinction between the capacity of doing something and the intentionality that puts it in action, while the third and fourth questions will be answered by means of dominant coalition theory and the viable system models. The model then will consists of the interactions of dominant coalitions within a viable system, which bargain and struggle over the means to use power and which have different forms, like coercion, preferences and cultural setting of power among others. Culture will be understood as a cosmovision, that is, the way in which a grouping of individuals conceive their environment and themselves in relation to one another, but also the communications that take place in ascertaining the content of such conceptions; that is, culture is at the same time a repository of information and the process in which this information is created or altered. Institutions are the interplay between Culture, Society and Power, they are the roles that different actors and coaltions have in their search for altering shared meanings and acceding collective resources, they are also the rules and values that inform such process and they are the shared meanings that revolve around power.